Creep performance of CNT polymer nanocomposites -An emphasis on viscoelastic interphase and CNT agglomeration. (1st July 2019) - Hassanzadeh-Aghdam, Mohammad Kazem; Mahmoodi, Mohammad Javad; Ansari, Reza
Abstract: The present work is aimed at presenting a multi-stage hierarchical micromechanical model to investigate creep response of polymer nanocomposites containing randomly dispersed carbon nanotubes (CNTs). Two frequently real situations-encountered fundamental aspects affecting the polymer nanocomposite mechanical behavior including the CNT/polymer interphase region and CNT agglomeration are taken into account. It is assumed that the CNT to be a transversely isotropic material and the polymer matrix obeys a viscoelastic constitutive law. The multi-stage procedure homogenizes the nanocomposite by exploiting a unit cell-based micromechanical model coupled with Eshelby method. Generally, an excellent agreement is found between the results of the current model and available experiment. The outcomes clearly prove that for a more realistic prediction in the case of creep performance of CNT-polymer nanocomposites, considering the (i) random dispersion and (ii) transversely isotropic behavior of CNTs as well as (iii) viscoelastic interphase region is essential. Moreover, when CNTs are not well-dispersed into the polymer nanocomposites, the three significant factors together with the CNTs agglomerated state must be precisely incorporated in the analysis to achieve a more accurate estimation of the creep response. It is shown that the CNT agglomeration dramatically influences and degrades the creep resistance of the CNT-polymer nanocomposites. Also, the effects of CNT volume fraction and interphase characteristics on the nanocomposites creep behavior are extensively examined. Graphical abstract: Image 1 Highlights: A multi-stage micromechanical modeling approach is presented to analyze the creep performance of CNT-reinforced polymer nanocomposites. The CNT/polymer interphase region and CNT agglomeration are taken into account in the analysis. The model predictions for nanocomposites containing uniformly dispersed CNT or agglomerated CNT agree well with experiments. Considering the random dispersion and transversely isotropic behavior of CNTs and also viscoelastic interphase is essential.